Risk Based Efficiency of Asian Banks -A Stochastic Approach of Cross Country Studies - An, Jiexue (2014)
Using stochastic cost frontier approach, this dissertation investigate the efficiency of 11 Asian region in the period of 1999-2013 in order to provide the general review of the efficiency in Asian banks. To estimate the stochastic cost frontier, a one-stage model has been adopted to estimate bank-specific variable, macro-economic variables and risk control variables in the cost frontier. The empirical result of the cost frontier summarized as below:1) the mean efficiency score of Asian banks is 0.83 ; 2)the most efficient banks is Japanese banks ;3) macroeconomic factors influence the cost efficiency of Asian banks